Synthesis of Nano Silver using Bioreductor of Tristaniopsis merguensis Leaf Extracts and Its Antibacterial Activity Test - Verry Andre Fabiani; Megawati Ayu Putri; Marhan Ebit Saputra; Della Puspita Indriyani (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2019)
Synthesis nanosilver from pelawan leaf extract (Tristaniopsis merguensis) has been carried out. The variables of this study were variations in the concentration of AgNO3 1 mM, 1.5 mM and 2 mM. Pelawan leaf extract acted as a bioreductor that converts Ag+ to Ag0. The synthesis was carried out in a ratio of 1: 4 (opposition leaf extract: AgNO3 solution) at 70 °C for 1.5 hours. The results of the UV-Vis analysis showed the maximum at the 1 mM; 1.5 mM; 2 mM AgNO3 concentration were 391 nm, 392 nm and 400 nm, respectively. XRD analysis explained that the resulting nanosilver was crystalline and according the Scherrer equation an average particle size was of 22.8 nm. The antibacterial activity test of nanosilver was carried out by disc method, nanosilver showed the existence of strong antibacterial activity against E. coli and S. aureus bacteria..